2019
DOI: 10.5397/cise.2019.22.1.9
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic-assisted Latissimus Dorsi Tendon Transfer for the Management of Irreparable Rotator Cuff Tears in Middle-aged Physically Active Patients

Abstract: Background: Latissimus dorsi (LD) tendon transfer is used as a treatment option for massive irreparable posterosuperior rotator cuff tears, and recently, an arthroscopic-assisted technique was introduced. This study was undertaken to evaluate the clinical and radiological outcomes of arthroscopic-assisted LD tendon transfer for the management of irreparable rotator cuff tears in active middle-aged patients.Methods: The records of five patients (two males) with irreparable tears involving the supraspinatus and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…This difference is of great impact on both the course of surgery and its outcomes. In 2019, Lim et al (11) described a series of aLDT using a dermal patch, whereas, in 2016, Kanath and colleagues (16) used a fascia lata autograft. The technique described in this study is in agreement with Kany's 2014 study (22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This difference is of great impact on both the course of surgery and its outcomes. In 2019, Lim et al (11) described a series of aLDT using a dermal patch, whereas, in 2016, Kanath and colleagues (16) used a fascia lata autograft. The technique described in this study is in agreement with Kany's 2014 study (22).…”
Section: Discussionmentioning
confidence: 99%
“…Over the years, several surgeries, or combinations thereof, have been proposed (5)(6)(7)(8)(9)(10). Among these, tendon transfers, initially studied for nerve injuries, are supported by biomechanical and clinical investigations describing their results in generally small to medium series (11)(12)(13)(14)(15)(16)(17)(18)(19). Transfer of the latissimus dorsi (LDT) on the greater tuberosity, at the level of the bicipital groove, transforms this muscle from an internal rotator to an external rotator (20,21).…”
Section: Introductionmentioning
confidence: 99%
“…Latissimus dorsi transfer has also been performed in patients with irreparable rotator cuff tears. Some investigators reported that latissimus dorsi transfer improved shoulder pain and function in physically active patients [ 8 , 21 ]. However, these were retrospective studies and the number of the subjects was small.…”
Section: What Are the Indications And Contraindications Of Scr?mentioning
confidence: 99%
“…Irreparable rotator cuff tear has various treatment options 10,19,23,26,28,34 ; however, superior capsular reconstruction (SCR) has been increasingly adopted in younger patients. 4,5,9,15,17,25,34 Mihata et al first reported graft healing in 20 of 24 patients (83%) who underwent SCR with autogenous tensor fascia lata (TFL).…”
mentioning
confidence: 99%